2009
DOI: 10.1149/1.3046150
|View full text |Cite
|
Sign up to set email alerts
|

Electro-osmosis and Water Uptake in Polymer Electrolytes in Equilibrium with Water Vapor at Low Temperatures

Abstract: Water uptake and electro-osmosis are investigated to improve the understanding and aid the modeling of water transport in proton-exchange membrane fuel cells ͑PEMFCs͒ below 0°C. Measurements of water sorption isotherms show a significant reduction in the water capacity of polymer electrolytes below 0°C. This reduced water content is attributed to the lower vapor pressure of ice compared to supercooled liquid water. At −25°C, 1100 equivalent weight Nafion in equilibrium with vapor over ice has 8 moles of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…5a and 18th minute in Fig. 5b), increasing liquid water mass under the landings moves in two directions; (1) in vertical (through-plane) direction such that from DM-under-the-landing into the flow channel through the DM-channel wall intersection, (2) in lateral (in-plane) direction within the DM such that from DMunder-the-landing to DM-under-the channel location. The water accumulation under the landing and removal of water through the 90 • interface is common for both cases.…”
Section: Effect Of Channel Wall Surface Hydrophobicity On Liquid Watementioning
confidence: 99%
See 1 more Smart Citation
“…5a and 18th minute in Fig. 5b), increasing liquid water mass under the landings moves in two directions; (1) in vertical (through-plane) direction such that from DM-under-the-landing into the flow channel through the DM-channel wall intersection, (2) in lateral (in-plane) direction within the DM such that from DMunder-the-landing to DM-under-the channel location. The water accumulation under the landing and removal of water through the 90 • interface is common for both cases.…”
Section: Effect Of Channel Wall Surface Hydrophobicity On Liquid Watementioning
confidence: 99%
“…In polymer electrolyte fuel cells (PEFCs), liquid water accumulation, transport and removal are critical, due to the significant impact on fuel cell operation and durability [1][2][3]. Experimental studies have shown that flooding inside a fuel cell may exist in the catalyst layer (CL), diffusion media (DM), flow channels or along the CL|DM interface [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…One has reasonably expected that water cannot freeze inside Nafion ® membrane since it is in a highly confined and acidic environment. When the temperature is decreased, the desorption property is driven by the ratio between the saturated vapor pressure over ice outside the membrane and the saturated vapor pressure of super-cooled water inside the membrane: this ratio is smaller than one and decreases upon cooling [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…At À20 C, and at a relative humidity of 100%, the approach used in the present work (based on the work of Gallagher et al 9 ) predicts a k of 8.2, whereas a relative humidity of 34% corresponds to 3.5. As discussed in Part I of this study, membrane hydration is often described by k, the moles of H 2 O per mole of SO À 3 in the membrane.…”
Section: Isothermal Parametric Studiesmentioning
confidence: 84%